The functions and targets of miR‐212 as a potential biomarker of cancer diagnosis and therapy. Issue 4 (13th January 2020) - Chen, Wenjun; Song, Jing; Bian, Hongjun; Yang, Xia; Xie, Xiaoyu; Zhu, Qiang; Qin, Chengyong; Qi, Jianni
Abstract: Cancer is a major health problem worldwide. An increasing number of researchers are studying the diagnosis, therapy and mechanisms underlying the development and progression of cancer. The study of noncoding RNA has attracted a lot of attention in recent years. It was found that frequent alterations of miRNA expression not only have various functions in cancer but also that miRNAs can act as clinical markers of diagnosis, stage and progression of cancer. MiR‐212 is an important example of miRNAs involved in cancer. According to recent studies, miR‐212 may serve as an oncogene or tumour suppressor by influencing different targets or pathways during the oncogenesis and the development and metastasis of cancer. Its deregulation may serve as a marker for the diagnosis or prognosis of cancer. In addition, it was recently reported that miR‐212 was related to the sensitivity or resistance of cancer cells to chemotherapy or radiotherapy. Here, we summarize the current understanding of miR‐212 functions in cancer by describing the relevant signalling pathways and targets. The role of miR‐212 as a biomarker and its therapeutic potential in cancer is also described. The aim of this review was to identify new methods for the diagnosis and treatment of human cancers.